MCNP-X code in radioactive particle tracking - Dam, Roos Sophia de Freitas; Salgado, César Marques (Instituto de Engenharia Nuclear: Progress Report, 2021)
A method based on the principles of the Radioactive Particle Tracking (RPT) technique is presented. Simulated geometry was performed with the MCNP-X code.